Anger tendency may be associated with duration of illness in panic disorder. Issue 1 (December 2015) - Sugaya, Nagisa; Yoshida, Eiji; Yasuda, Shin; Tochigi, Mamoru; Takei, Kunio; Otowa, Takeshi; Umekage, Tadashi; Konishi, Yoshiaki; Sakano, Yuji; Nomura, Shinobu; Okazaki, Yuji; Kaiya, Hisanobu; et al.
Abstract Background Several studies have reported an increased tendency towards anger in patients with panic disorder (PD). If this propensity for anger arises from the pathological process of PD, it may be associated with the duration of the illness. The present study therefore examined the relationship between duration of PD and the personality tendency to experience anger in PD patients. Methods Participants were 413 patients (132 men and 281 women; age = 38.7 years) with PD. Diagnoses were confirmed using the Mini-International Neuropsychiatric Interview. Illness duration ranged from less than a year to 51 years. After participants completed the Revised NEO Personality Inventory, we examined the association between illness duration and the Angry Hostility and Impulsiveness subscale scores. In the analysis, participants were divided into two groups by duration of illness (long group, n = 186 and short group, n = 200) using the median value (9 years) as a cut-off because of the skewed distribution of the duration. Patients with an illness duration of 9 years (n = 27) were excluded from the comparison. Results The duration of illness was significantly correlated with the Angry Hostility score (p = 0.002) after controlling for age. Scores were significantly higher in the long group than in the short group (p = 0.04). No significant association was observed between Impulsiveness scores and duration of illness. Conclusion The present study suggests that longer PD duration is related to a stronger tendency to experience anger.